Influenza A (H1N1pdm09)-Related Critical Illness and Mortality in Mexico and Canada, 2014*. Issue 10 (October 2016) - Dominguez-Cherit, Guillermo; De la Torre, Alethse; Rishu, Asgar; Pinto, Ruxandra; Ñamendys-Silva, Silvio A.; Camacho-Ortiz, Adrián; Silva-Medina, Marco Antonio; Hernández-Cárdenas, Carmen; Martínez-Franco, Michel; Quesada-Sánchez, Alejandro; López-Gallegos, Guadalupe Celia; Mosqueda-Gómez, Juan L.; et al.
Abstract : Objectives: The 2009–2010 influenza A (H1N1pdm09) pandemic caused substantial morbidity and mortality among young patients; however, mortality estimates have been confounded by regional differences in eligibility criteria and inclusion of selected populations. In 2013–2014, H1N1pdm09 became North America's dominant seasonal influenza strain. Our objective was to compare the baseline characteristics, resources, and treatments with outcomes among critically ill patients with influenza A (H1N1pdm09) in Mexican and Canadian hospitals in 2014 using consistent eligibility criteria. Design: Observational study and a survey of available healthcare setting resources. Setting: Twenty-one hospitals, 13 in Mexico and eight in Canada. Patients: Critically ill patients with confirmed H1N1pdm09 during 2013–2014 influenza season. Interventions: None. Measurements and Main Results: The main outcome measures were 90-day mortality and independent predictors of mortality. Among 165 adult patients with H1N1pdm09-related critical illness between September 2013 and March 2014, mean age was 48.3 years, 64% were males, and nearly all influenza was community acquired. Patients were severely hypoxic (median PaO2 -to-FIO2 ratio, 83 mm Hg), 97% received mechanical ventilation, with mean positive end-expiratory pressure of 14 cm H2 O at the onset of critical illness and 26.7% received rescue oxygenation therapy with prone ventilation, extracorporeal life support, high-frequency oscillatory ventilation, or inhaled nitric oxide. At 90 days, mortality was 34.6% (13.9% in Canada vs 50.5% in Mexico, p < 0.0001). Independent predictors of mortality included lower presenting PaO2 -to-FIO2 ratio (odds ratio, 0.89 per 10-point increase [95% CI, 0.80–0.99]), age (odds ratio, 1.49 per 10 yr increment [95% CI, 1.10–2.02]), and requiring critical care in Mexico (odds ratio, 7.76 [95% CI, 2.02–27.35]). ICUs in Canada generally had more beds, ventilators, healthcare personnel, and rescue oxygenation therapies. Conclusions: Influenza A (H1N1pdm09)-related critical illness still predominantly affects relatively young to middle-aged patients and is associated with severe hypoxemic respiratory failure. The local critical care system and available resources may be influential determinants of patient outcome. Abstract : Supplemental Digital Content is available in the text.